Synthesis of acrylates from olefins and CO2 using sodium alkoxides as bases - Manzini, Simone; Trapp, Oliver; Schaub, Thomas (Catalysis today, 2017)
We have discovered a simple procedure for an industrially applicable alternative synthesis of sodium acrylate via the catalytic carboxylation of ethylene with CO2. We identified tert-butoxide as suitable base in this catalytic transformation, which was excluded in previous reports, based on investigations on the stability of the corresponding carbonates. In addition, we were able to access a completely zinc-free procedure for the sodium acrylate formation by introducing a regeneration step during the catalyst recycle. Due to the basicity of the sodium tert-butoxide, it was also possible to carboxylate different terminal and internal olefins, which could not be achieved using the previously reported nickel system using phenolate bases.